IMPLEMENTATION OF LEGAL PROTECTION BY THE GOVERNMENT IN ORDER TO EMPOWERMENT OF MICRO SMALL MEDIUM ENTERPRISE TO REALIZE THE JUSTICE ECONOMY (Research Study: The Office of Cooperative and Micro Small and Medium Enterprise Province of Central Java) - Raden Ani Eko Wahyuni; Darminto Hartono (Diponegoro Law Review, 2019)
Micro, Small and Medium Enterprises try to grow and develop their business in order to build a national economy based on equitable economic democracy. The position of MSMEs is very important in economic development It is very important to do protection. Protection of MSMEs is assistance and support made by the government towards MSMEs. Protection in legal action, assistance in the production process to marketing and support in terms of capital. There is a debate that is found is how to issue law by the government in empowering MSMEs to realize equitable economic prosperity.The research in this paper used a normative juridical research method. The approach used in this study is socio legal approach which the law is conceptualized as a set of regulation that is valid in the society and the validity will be affected by other factors.This study intends to measure the extent of the role of the government and what efforts are being made especially by regional governments, in this case the Central Java Provincial Office of Cooperatives and SMEs in implementing legal protection in empowering MSMEs to realize economic welfare.